### Теория:

Multiplication:
When more than $$2$$ numbers are multiplied, depending upon the number of negative numbers involved, the sign of the answer varies.
We know that,
$$(-1) × (1) = -1$$
$$(-1) × (-1) = +1$$

Now,
$$(-1) × (-2) × (-3) = -6$$
$$(-1) × (-2) × (-3) × (-4) = +24$$
$$(-1) × (-2) × (-3) × (-4) × (-5) = -120$$

Inference:
When $$2$$ negative numbers are multiplied, the result will be a positive number.
When $$3$$ negative numbers are multiplied, the result will be a negative number.
When $$4$$ negative numbers are multiplied, the result will be a positive number.

Conclusion:
From the above, we can conclude that,
 Number of negative integers in multiplication Sign of the result Even $$+$$ odd $$-$$

Division:
Let's learn, how to deal with the division of more than $$2$$ numbers, $$a,b,c$$ are three numbers, $$a/b/c$$ should be evaluated as $$(a×c)/b$$.
Example:
$\begin{array}{l}1.\phantom{\rule{0.147em}{0ex}}\frac{1/2}{3}=\frac{1×3}{2}=\frac{3}{2}\\ \\ 2.\phantom{\rule{0.147em}{0ex}}\frac{2/6}{5}=\frac{2×5}{6}=\frac{10}{6}\end{array}$
$$a,b,c,d$$ are four numbers, a/b/c/d should be evaluated as $$(a×d)/(b×c)$$
Example:
$\begin{array}{l}1.\phantom{\rule{0.147em}{0ex}}\frac{5/2}{3/6}=\frac{5×6}{3×2}=\frac{30}{6}\\ \\ 2.\phantom{\rule{0.147em}{0ex}}\frac{2/6}{5/2}=\frac{2×2}{5×6}=\frac{4}{30}\\ \\ 3.\phantom{\rule{0.147em}{0ex}}\frac{2/4}{6/2}=\frac{2×2}{6×4}=\frac{4}{24}\end{array}$
Similar to multiplication, when more than $$2$$ numbers are involved, depending upon the number of negative numbers involved, the sign of the answer varies.
 Number of negative integers in division Sign of the result Even $$+$$ odd $$-$$
Example:
$\begin{array}{l}1.\phantom{\rule{0.147em}{0ex}}\frac{-5/-2}{-2/8}=\frac{-5×8}{-2×-2}=\frac{-40}{4}\\ \\ 2.\phantom{\rule{0.147em}{0ex}}\frac{-8/-6}{2/4}=\frac{-8×4}{-6×2}=\frac{-32}{-12}=\frac{32}{12}\\ \\ 3.\phantom{\rule{0.147em}{0ex}}\frac{-9/1}{-1/6}=\frac{-9×6}{-1×1}=\frac{-54}{-1}=\frac{54}{1}\\ \\ 4.\phantom{\rule{0.147em}{0ex}}\frac{-1/2}{1/2}=\frac{-1×2}{1×2}=\frac{-2}{2}=-1\\ \\ 5.\phantom{\rule{0.147em}{0ex}}\frac{\frac{-1}{2}}{2}=\frac{-1×2}{2×1}=-1\end{array}$